Patterns and drivers of fungal disease communities on Arabica coffee along a management gradient - Zewdie, Beyene; Tack, Ayco J.M.; Adugna, Girma; Nemomissa, Sileshi; Hylander, Kristoffer (Basic and applied ecology, 2020)
Plants, including those managed by humans, are often attacked by multiple diseases. Yet, most studies focus on single diseases, even if the disease dynamics of multiple species is more interesting from a farmers’ perspective. Moreover, most studies are from single management systems, although it is valuable to understand how diseases are distributed across broad management gradients, especially in cases where less intensive management also provides biodiversity values in the landscape. To understand the spatial dynamics and drivers of diseases across such a broad management gradient, we assessed four major fungal diseases on Arabica coffee (Coffea arabica) at 60 sites in southwestern Ethiopia along a gradient from only little managed wild coffee in the forest understory to intensively managed coffee plantations. We found that environmental and management factors related to disease incidence and severity differed strongly among the four fungal diseases. Coffee leaf rust (Hemileia vastatrix) and Armillaria root rot (Armillaria mellea) were more severe in intensively managed sites, whereas coffee berry disease (Colletotrichum kahawae) and wilt disease (Gibberella xylarioides) were more severe in less managed sites. Among sites, incidence and severity of the four fungal diseases poorly correlated with each other. Within sites, however, shrubs that were severely attacked by coffee leaf rust also had high levels of berry disease symptoms. A better understanding of disease dynamics is important for providing management recommendations that benefit smallholder farmers, but also to evaluate possibilities for maintaining biodiversity values in the landscape related to shade cover complexity and wild coffee genetic variation.